2021
DOI: 10.1136/sextrans-2020-054840
|View full text |Cite
|
Sign up to set email alerts
|

Sexual consent and chemsex: a quantitative study on sexualised drug use and non-consensual sex among men who have sex with men in Amsterdam, the Netherlands

Abstract: BackgroundChemsex (drug use to enhance sex) has emerged among men who have sex with men (MSM). Non-consensual sex (NCS) is hypothesised to occur frequently under the influence of chemsex, however data are scarce. In this cross-sectional study, it was aimed to assess whether NCS is associated with chemsex.MethodsWe offered a survey about chemsex in the past 6 months (crystal methamphetamine, mephedrone and/or gamma-hydroxybutyrate/gamma-butyrolacton use) and NCS (sexual experiences beyond one’s limits or unplea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…35 Non-consensual sexual activity can be associated with chemsex. 62 Death from unintentional overdose may also be seen. 63 Progression from occasional use to more pervasive substance use disorder can occur.…”
Section: Other Associated Problemsmentioning
confidence: 99%
“…35 Non-consensual sexual activity can be associated with chemsex. 62 Death from unintentional overdose may also be seen. 63 Progression from occasional use to more pervasive substance use disorder can occur.…”
Section: Other Associated Problemsmentioning
confidence: 99%
“…Some chemsex participants also report being the victim of nonconsensual sex while under the influence of drugs [ 2 , 60 ]. A recent study among MSM in Amsterdam showed that 41.4% of the participants who engage in chemsex reported passing out and not remembering what happened while under the influence of drugs [ 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…People with existing mental health conditions (including in the GDS) reported greater increases in drinking during the pandemic [ 74 , 79 ]. Among men partnered with men in our sample, increased drinking potentially contributed to the higher prevalence of experiencing sexual abuse [ 74 , 80 , 81 ]. One study reported that experiencing IPVA during restrictions was positively associated with the number of casual sexual partners that men in a relationship with men met during the pandemic [ 15 ].…”
Section: Discussionmentioning
confidence: 99%